Disability and labor market outcomes - Melanie Jones (IZA World of Labor, 2016)
In Europe, about one in eight people of working age report having a disability; that is, the presence of a long-term limiting health condition. Despite the introduction of a range of legislative and policy initiatives designed to eliminate discrimination and facilitate retention of and entry into work, disability is associated with substantial and enduring employment disadvantages. Identifying the reasons for this is complex, but critical to determine effective policy solutions that reduce the social and economic costs of disability disadvantage.
Keywords: J14; J31; J24; J71; 330; disability; discrimination; employment; earnings